GLOBAL VALUES IN LOCAL WISDOM BASED MANAGEMENT ACCOUNTING FOR THE DEVELOPMENT OF RELIGIOUS HIGHER EDUCATION - Nur Fitry Latief; Youlanda Hasan (SOSIOEDUKASI, 2026)
This study aims to analyze, evaluate, and develop an in-depth exploration of the local cultural philosophy “Biar Kalah Nasi Mar Jang Kalah Aksi” as the foundation for formulating a new concept in management accounting to strengthen the global competitiveness of state religious higher education institutions. A qualitative research method with a descriptive ethnographic approach was employed to collect data through in-depth interviews with informants from 15 cities and regencies in North Sulawesi Province, as well as those residing outside the province, particularly key informants with a deep understanding of this local wisdom. The findings reveal that this cultural philosophy embodies values of resilience, innovation, and efficiency under conditions of limitation, which can be integrated into management accounting systems as an adaptive model for addressing global challenges while preserving local identity. Furthermore, the application of these values has the potential to optimize resource management and reinforce the institutional identity of state religious higher education institutions in responding to global changes and demands. The novelty of this study lies in the development of a local wisdom–based management accounting concept that is not only culturally relevant but also provides a responsive and sustainable foundation for the advancement of state religious higher education institutions.